The Early diagnosis of infiltration neoplastic lymphatic pathway - Priario, Julio C (Cirugía del Uruguay, 2002)
Cancer is currently dominated in its initial stage (localized lesion) but escapes from our control when it spreads through the lymphatic pathway or by blood. So the current tactic is to discover neoplastic contamination at the stage preclinical